Karakteristik Anthropometrik Penduduk Pulau Palue - Josef Glinka, Josef Glinka (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1984)
The island of Palue belongs to the Lesser Sunda Archipelago on 121ÃÂ° 43 East and 8ÃÂ° 20 South, some 15 km north of Central Flores. The anthropometrical material given here was collected in 1966/67 by the author, At that time the island was a biological isolate. The number of individuals is 526 men and 296 women.Key Words: Indonesia - Lesser Sunda Islands - Palue - anthropometry - biological isolate